PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA INTERAKTIF MENGGUNAKAN ADOBE FLASH CS.5 MENULIS TEKS EKSPLANASI KOMPLEKS - Indry Dwi Prezky (LPPM STIKes SITI HAJAR dan Insight Power, 2023)
The goal of this study is to develop multimedia-based media using Adobe Flash CS.5 and determine the outcomes of the ability to write complex explanatory text, which is in contrast to learning issues that are the teacher's responsibility because the method of instruction cannot be packaged in an attractive manner for the times. As a result, the study's goal was to create interactive multimedia-based learning materials utilizing Adobe Flash CS.5 on a difficult explanation text in order to assess participants' writing skills. The research methodology employs a research and development approach.Keywords: complex explanatory text; interactive multimedia; research and development.